2008
DOI: 10.1161/circep.107.754564
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Remodeling and Atrial Fibrillation

Abstract: A trial fibrillation (AF) is the most common arrhythmia in clinical practice. It can occur at any age but is very rare in children and becomes extremely common in the elderly, with a prevalence approaching 20% in patients Ͼ85 years of age. 1 AF is associated with a wide range of potential complications and contributes significantly to population morbidity and mortality. Present therapeutic approaches to AF have major limitations, including limited efficacy and significant adverse effect liability. These limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
669
0
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 907 publications
(698 citation statements)
references
References 126 publications
17
669
0
12
Order By: Relevance
“…Furthermore, we showed that the inhibitory effect of rapid pacing on LTCC function was antagonized by silencing the expression of ZnT-1 (31). Analysis of human atrial samples collected during heart surgery revealed increased expression of ZnT-1 in patients suffering from atrial fibrillation as compared with patients in sinus rhythm (31) implying a role for ZnT-1 in the LTCC dysfunction that is believed to play an important role in the pathophysiology of this common arrhythmia (9,41).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we showed that the inhibitory effect of rapid pacing on LTCC function was antagonized by silencing the expression of ZnT-1 (31). Analysis of human atrial samples collected during heart surgery revealed increased expression of ZnT-1 in patients suffering from atrial fibrillation as compared with patients in sinus rhythm (31) implying a role for ZnT-1 in the LTCC dysfunction that is believed to play an important role in the pathophysiology of this common arrhythmia (9,41).…”
mentioning
confidence: 87%
“…They also modulate Ca 2ϩ homeostasis, hormone secretion, phosphorylation processes, and gene regulation (8). In addition, alterations in LTCC function have been linked to several pathophysiologies, such as cardiac arrhythmias (1,9), cardiac hypertrophy and failure (10,11), abnormal insulin secretion (12), and severe multisystemic congenital abnormalities (13).…”
mentioning
confidence: 99%
“…13,153,154,190 A number of ion channel modifications underlying such electrical changes have been described in animal models and humans. 17,190,191,192 A recent study 158 used a clinically relevant ovine model of intermittent RA tachypacing and demonstrated that, after the first AF episode, the dominant excitation frequency (DF) increased gradually during a 2-week period in both LA and RA until it stabilized at a time that coincided with the onset of persistent AF.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…The generally poor outcome with current antiarrhythmic drugs likely reflects the fact that most of the used agents were developed in the absence of precise understanding of pro-and anti-arrhythmic drug actions and the arrhythmogenic disease-specific cardiac substrate. Conceptually, AF induction requires a vulnerable substrate and a trigger that acts on the substrate to initiate the arrhythmia [25,35]. Once AF is initiated, the rapid-atrial rate creates progressive AF-related changes in atrial electrical and structural properties (atrial remodeling).…”
mentioning
confidence: 99%
“…signaling, whereas increased atrial fibrosis and heterogeneous conduction slowing are typical characteristics of structural remodeling. Atrial remodeling can promote ectopic (triggered) activity and facilitate reentry, thereby contributing to AF perpetuation and the progression from short-lasting (paroxysmal) to long-standing persistent AF [7,10,25,26,35], which makes AF more resistant to both pharmacological and nonpharmacological therapeutic approaches. Therefore, it is assumed that a better understanding of the molecular mechanisms underlying AF maintenance will help to design novel drugs with improved efficacy and safety profiles [8].…”
mentioning
confidence: 99%